2021
DOI: 10.1177/13670069211033032
|View full text |Cite
|
Sign up to set email alerts
|

‘The English language enables me to visit my pain’. Exploring experiences of using a later-learned language in the healing journey of survivors of sexuality persecution

Abstract: Aims and objectives: This qualitative study explores the experience of using a later-learned language, English (ELX), in the therapeutic journey of refugee survivors of sexuality persecution to enhance understanding of the role of language in their rehabilitation. Design/methodology/approach: This is a multiple case study of three refugees, persecuted in their home country because of their sexual orientation, who are regular attendees of a therapeutic community, Room to Heal, based in London. A qualitatively d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 42 publications
(66 reference statements)
3
15
0
Order By: Relevance
“…The results of the interviews also demonstrated the essential role that therapists' understanding of their own and their clients' languages plays in discussing emotionally sensitive topics (e.g., family relations, memories, etc.). The participants' observations of closer emotional involvement in L1 than in LX confirms earlier work on multilingualism and emotion (Cook & Dewaele, 2021;Dewaele, 2013;Dewaele & Costa, 2013;Kokaliari et al, 2013;Moate & Ruohotie-Lyhty, 2017;Panicacci & Dewaele, 2017. Our study demonstrated that the sensitivity of emotional encoding and decoding to the language in which it is expressed seems to be particularly relevant when discussing traumatic events (Cook, 2019).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The results of the interviews also demonstrated the essential role that therapists' understanding of their own and their clients' languages plays in discussing emotionally sensitive topics (e.g., family relations, memories, etc.). The participants' observations of closer emotional involvement in L1 than in LX confirms earlier work on multilingualism and emotion (Cook & Dewaele, 2021;Dewaele, 2013;Dewaele & Costa, 2013;Kokaliari et al, 2013;Moate & Ruohotie-Lyhty, 2017;Panicacci & Dewaele, 2017. Our study demonstrated that the sensitivity of emotional encoding and decoding to the language in which it is expressed seems to be particularly relevant when discussing traumatic events (Cook, 2019).…”
Section: Discussionsupporting
confidence: 84%
“…English LX made it possible to recount the traumatic experience which occurred in their L1 without being overwhelmed by despair. As one participant put it: "The English language enables me to visit my pain" (Cook & Dewaele, 2021). English LX allowed them to enhance their self-esteem and confidence.…”
Section: Languages and Emotion In Psychotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…The last subsection in this present review includes seven studies (Brune et al, 2011; Cook & Dewaele, 2022; Dewaele & Costa, 2013; Ibarra, 2021; Schwanberg, 2010; Szoke et al, 2020; Verkerk et al, 2021) that investigate the issue of treating trauma in multiple languages. Five of the studies (Brune et al, 2011; Cook & Dewaele, 2022; Ibarra, 2021; Schwanberg, 2010; Szoke et al, 2020) have trauma treatment and language as their primary focus, whereas the remaining two (Dewaele & Costa, 2013; Verkerk et al, 2021) mention this among their findings.…”
Section: Resultsmentioning
confidence: 99%
“…Switching to the LX allows multilingual clients in psychotherapy to either zoom in or out depending on whether they need to distance themselves from the traumatic event they are discussing (Costa & Dewaele, 2014, 2019Rolland, Costa, & Dewaele, 2021;Rolland, Dewaele, & Costa, 2017). Cook and Dewaele (2021) multiple case study on the language preferences of three refugees who had been tortured in their homeland because of their sexual orientation before starting therapy in the UK showed that some experiences were just too traumatic to retell in their L1 but that the use of English (LX) enabled them "to visit their pain" as one participant put it.…”
Section: Self-report Methodsmentioning
confidence: 99%